2015
DOI: 10.1021/acs.energyfuels.5b00110
|View full text |Cite
|
Sign up to set email alerts
|

2,3,6-/2,3,4-Aryl Isoprenoids in Paleocene Crude Oils from Chinese Jianghan Basin: Constrained by Water Column Stratification

Abstract: 2,3,4-Trimethyl aryl isoprenoid (AIP) hydrocarbons as well as their 2,3,6 homologues were found in most Paleocene crude oils from the Jianghan Basin, China. We interpret their concurrence as evidence for the presence of both purple sulfur bacteria (PSB, family of Chromatiaceae) and green sulfur bacteria (GSB, family of Chlorobiaceae) in the water body during deposition. The GSB and PSB contributions are also evidenced by the presence of the monoaromatic carotenoid derivatives chlorobactane and okenane as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…The 2,3,6-TMAI biomarkers are breakdown products of the carotenoid pigments of "brown" strains of anoxygenic phototrophic green sulfur bacteria (GSBs). Their presence, therefore, is typically ascribed to the presence of an anoxygenic phototrophic population in an anoxic water-column setting (73,74).…”
Section: The Depositional Environment and Source Of Fementioning
confidence: 99%
“…The 2,3,6-TMAI biomarkers are breakdown products of the carotenoid pigments of "brown" strains of anoxygenic phototrophic green sulfur bacteria (GSBs). Their presence, therefore, is typically ascribed to the presence of an anoxygenic phototrophic population in an anoxic water-column setting (73,74).…”
Section: The Depositional Environment and Source Of Fementioning
confidence: 99%
“…MTTCs were mainly identified in the evaporite-related source rocks and crude oils (Figure a). The evaporite-related source rocks contain varying lithology types including mudstone, black shale, marl, halite deposits, etc. The organic matter abundances of these evaporite-related source rocks vary greatly from organic-rich to organic-lean and contained type I, type II, and type III kerogens. Based on previous studies, we found that source rocks containing MTTCs were not widely distributed globally; they were found mainly in salt-bearing sedimentary basins in China and Europe. , By comparing Figure a and Figure b, we found that evaporite-related source rocks were globally distributed, while MTTCs were not detected in most of these evaporite-related organic sediments. There are two possible reasons that may explain this situation.…”
Section: Distribution Of Mttcsmentioning
confidence: 75%
“…23−31 Based on previous studies, we found that source rocks containing MTTCs were not widely distributed globally; they were found mainly in salt-bearing sedimentary basins in China and Europe. 32,33 By comparing Figure 2a and Figure 2b, we found that evaporite-related source rocks were globally distributed, 34 while MTTCs were not detected in most of these evaporite-related organic sediments. There are two possible reasons that may explain this situation.…”
Section: ■ Distribution Of Mttcsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure 23 gives a general illustration of euxinic environments with the presence of sulfur bacteria, the main source for specific aromatic carotenoids (e.g., isorenieratane) in sedimentary environments and are molecular indicators of photic zone euxinia (PZE). Other important occurrences of carotenoids are in sponge species; since these organisms cannot biosynthesize such compounds, their presence is due to the symbiotic relationship (LU et al, 2015).…”
Section: Aromatic Carotenoids and Aryl Isoprenoidsmentioning
confidence: 99%